Combinatorial screening of halide perovskite thin films and solar cells by mask-defined IR laser molecular beam epitaxy. Issue 1 (31st December 2017) - Kawashima, Kazuhiro; Okamoto, Yuji; Annayev, Orazmuhammet; Toyokura, Nobuo; Takahashi, Ryota; Lippmaa, Mikk; Itaka, Kenji; Suzuki, Yoshikazu; Matsuki, Nobuyuki; Koinuma, Hideomi
Abstract: As an extension of combinatorial molecular layer epitaxy via ablation of perovskite oxides by a pulsed excimer laser, we have developed a laser molecular beam epitaxy (MBE) system for parallel integration of nano-scaled thin films of organic–inorganic hybrid materials. A pulsed infrared (IR) semiconductor laser was adopted for thermal evaporation of organic halide (A-site: CH3 NH3 I) and inorganic halide (B-site: PbI2 ) powder targets to deposit repeated A/B bilayer films where the thickness of each layer was controlled on molecular layer scale by programming the evaporation IR laser pulse number, length, or power. The layer thickness was monitored with an in situ quartz crystal microbalance and calibrated against ex situ stylus profilometer measurements. A computer-controlled movable mask system enabled the deposition of combinatorial thin film libraries, where each library contains a vertically homogeneous film with spatially programmable A- and B-layer thicknesses. On the composition gradient film, a hole transport Spiro-OMeTAD layer was spin-coated and dried followed by the vacuum evaporation of Ag electrodes to form the solar cell. The preliminary cell performance was evaluated by measuring I - V characteristics at seven different positions on the 12.5 mm × 12.5 mm combinatorial library sample with seven 2 mm × 4 mm slits under a solar simulator irradiation. The combinatorial solar cell library clearly demonstrated that the energy conversion efficiency sharply changes from nearly zero to 10.2% as a function of the illumination area in the library. The exploration of deposition parameters for obtaining optimum performance could thus be greatly accelerated. Since the thickness ratio of PbI2 and CH3 NH3 I can be freely chosen along the shadow mask movement, these experiments show the potential of this system for high-throughput screening of optimum chemical composition in the binary film library and application to halide perovskite solar cell. Abstract :